Civilization: history, description, common characteristics and importance - Sulaiman, Kabuye Uthman (Zes Rokman Resources, 2016)
Civilization is a characteristic of people; it is one of the things that set human beings apart from other species.i While it is true that all living things form societies, it is only human beings who have a civilization. A civilization provides man with numerous basic needs and wants. The primary aim of this paper is to expound these needs and wants. They are classified as follows: (a) physical and material (economic) needs, such as shelter, food, clothing and tools, (b) spiritual and psychic (religious) needs, such as a worldview, (c) intellectual needs, (d) gregarious (social) needs, such as companionship and interrelationships between people, (e) military,ii (f) technological needs, and (g) cultural needs. The paper will also provide an overview of the following: firstly, history of civilization; secondly, a description of civilized vs. pre-civilized communities, simple civilizations vs. advanced civilizations; thirdly, an outline of the key components that make up a civilization; and fourthly, an explanation of the reasons for the invention of civilization. The study argues that: firstly, civilization is vital to man’s living, without it solidarity, cooperation and fraternity among people of different nations cannot be achieved; secondly, every civilization, regardless of its size and lifespan, has contributed tremendously to other civilizations. Hence, no community should be labeled as ‘primitive.’ It is expected that this study will contribute to understanding the importance of civilization, its history, description, elements and characteristics.